THE ROLE OF BIBLIOMETRIC ANALYSIS OF ARTIFICIAL INTELLIGENCE (AI) IN ACCOUNTING: A STUDY FROM SCIENCEDIRECT, EMERALD INSIGHT, AND SCOPUS DATABASES - Taufiqurrahman, Muhammad; Lating, Ade Irma Suryani (International Journal of Accounting Innovation, 2025)
Objective: This study aims to examine publication trends related to AI in accounting using a bibliometric approach, by identifying influential authors, key keywords, and patterns of scientific collaboration. Method: Research data was taken from 50 publications on the Scopus, ScienceDirect, and Emerald Insight databases between 2021 and 2025, and then analyzed using VOSviewer 1.6.20 software with co-authorship and co-occurrence techniques. Results: The analysis results confirm that "artificial intelligence" is the most dominant keyword, while visualizations in the form of networks, overlays, and densities reveal the collaboration structure and the development of research themes. Novelty: This study provides a comprehensive mapping of AI literature in accounting and can be an important reference for both researchers and practitioners in identifying emerging trends and issues.